A design of cascade control system and adaptive load compensator for battery/ultracapacitor hybrid energy storage-based direct current microgrid. (15th April 2016) - Pavković, Danijel; Lobrović, Mihael; Hrgetić, Mario; Komljenović, Ante
Highlights: Battery/ultracapacitor storage is considered for a direct-current microgrid. Microgrid voltage cascade control system with load compensator is designed. Current references are allocated so that ultracapacitor takes on transient loads. Adaptive Kalman filter-based estimator is used for indirect load compensation. Control strategy has been verified on a downscaled hardware-in-the-loop setup. Abstract: A control system design based on an actively-controlled battery/ultracapacitor hybrid energy storage system suitable for direct current microgrid energy management purposes is presented in this paper. The proposed cascade control system arrangement is based on the superimposed proportional–integral voltage controller designed according to Damping Optimum criterion and a zero-pole canceling feed-forward load compensator aimed at voltage excursion suppression under variable load conditions. The superimposed controller commands the inner battery and ultracapacitor current control loops through a dynamic current reference distribution scheme, wherein the ultracapacitor takes on the highly-dynamic (transient) current demands, and the battery covers for steady-state loads. In order to avoid deep discharges of the ultracapacitor module, it is equipped with an auxiliary state-of-charge controller. Finally, for those applications where load is not measured, an adaptive Kalman filter-based load compensator is proposed and tested. The presented control strategy has been implemented on the low-cost industrial controller unit, and its effectiveness has been verified by means of simulations and experiments for the cases of abrupt load changes and quasi-stochastic load profiles using a downscaled battery/ultracapacitor hardware-in-the-loop experimental setup.